2016
DOI: 10.1111/jocn.13140
|View full text |Cite
|
Sign up to set email alerts
|

The unmet supportive care needs of long‐term head and neck cancer caregivers in the extended survivorship period

Abstract: Health professionals should be aware that a minority of long-term head and neck caregivers continue to experience strong fears of cancer recurrence. To reduce unmet needs across multiple domains, health professionals should seek to reduce caregivers' feelings of loneliness, and to assist caregivers to reduce the financial burdens that they experience as a result of long-term caring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
2
31
0
5
Order By: Relevance
“…9 A study of long-term caregivers of patients with head and neck cancer also found greatest levels of unmet needs for partners of patients to occur in the emotional and health service domains. 10 Head and neck patients with cancer are at high risk for emotional and financial distress, and in our survey depression/anxiety and the associated body and self-image issues are less commonly addressed by respondents. The incidence of depression in patients with HNC is as high as 40%.…”
Section: Discussionmentioning
confidence: 91%
“…9 A study of long-term caregivers of patients with head and neck cancer also found greatest levels of unmet needs for partners of patients to occur in the emotional and health service domains. 10 Head and neck patients with cancer are at high risk for emotional and financial distress, and in our survey depression/anxiety and the associated body and self-image issues are less commonly addressed by respondents. The incidence of depression in patients with HNC is as high as 40%.…”
Section: Discussionmentioning
confidence: 91%
“…These results are in contrast to 2 previous studies in, respectively, patients with newly diagnosed oral cancer 8 and patients with mixed head and neck cancer up to 5 years after head and neck cancer diagnosis, 3 which found no head and neck cancer-specific unmet needs among its top 10. 27,28 Whether these needs among head and neck cancer caregivers are comparable to those of caregivers of a more homogeneous group of patients who underwent total laryngectomy needs, however, needs to be further investigated. In the study of Wells et al, 4 in mixed patients with head and neck cancer 3 months to 5 years after treatment, comparable with our findings, multiple head and neck cancer-specific unmet needs were reported among its top 10, including needs regarding dry mouth, dental health, swallowing, speech, chewing and eating, and taste loss.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although recently published research among caregivers of patients with head and neck cancer indicated that the perceived burden from the caregivers' perspective was relatively low, 27 about half of all caregivers report at least 1 moderate to high unmet need. 27,28 Whether these needs among head and neck cancer caregivers are comparable to those of caregivers of a more homogeneous group of patients who underwent total laryngectomy needs, however, needs to be further investigated. A currently ongoing Dutch longitudinal cohort study measures supportive care needs among caregivers of patients with head and neck cancer using the caregivers version of the SCNS (ie, the SCNS-P&C), 29 enabling the opportunity to investigate supportive care needs of both head and neck cancer and total laryngectomy caregivers in more detail (over time).…”
Section: Discussionmentioning
confidence: 99%
“…De este modo, se puede observar que los familiares de supervivientes de cáncer tienen necesidades psicológicas, en particular en relación con el estrés y con hacer frente a la carga de proporcionar un cuidado físico junto con la preocupación por la salud del superviviente 19 , las dificultades en la gestión de sus propias respuestas emocionales al tiempo que proporcionan apoyo a los demás 27,29 , las preocupaciones sobre el futuro de la persona que cuidan 23,26,30 y ayuda para encontrar un sentido de esperanza 23 . Especialmente cuando se ha evidenciado que los familiares muestran angustia emocional incluso a los cincos años del diagnóstico 25 .…”
Section: Necesidad De Apoyo Emocional Y Espiritualunclassified
“…La información es una de las necesidades prioritarias de los familiares en la etapa de larga supervivencia 29,30 . Éstos solicitan información sobre cuestiones muy diversas tales como: el diagnostico de cáncer 25 , los beneficios y efectos secundarios del tratamiento 27 , el pronóstico del paciente superviviente 21 , las posibilidades de recidiva 19 , información sobre el riesgo familiar y consejo genético 21 e información acerca de cobertura sanitaria y seguros médicos así como ayudas económicas por incapacidad laboral 25,27,30 .…”
Section: Necesidad De Informaciónunclassified